(3TQM GddeY aj GdfMhs - (3CHh fUQ GdbGSe Hf eMeO Hf GdefGTjQ GdJHQjRi GdhGSWis; (3GHf Lfj , CHh GdaJM YKeGf Hf Lfj GdehUdj, GHf Lfj,J (B392 (3g` s
(3ChdgG (B:s
(3bGd CHh GdaJM YKeGf Hf Lfi QMeg Gddg GdcdGe cdg KdGKI CTjGA GSe haYd hMQa LGA deYfi bGd GdeaSQ GdcdGe cdg YQHjI hYLejI dG jNdhG ef Cf jchf CSekG haYdkG hMQakG s
(3BNQgG (B:s
(3hdCf GdMLGL hGdYLGL YdeGf hGdCYdGe cKjQkG eG jZjQ hdjS gPG HbjGS EfeG jbY SeGYkG adG jMed Ydjg ZjQg Je GdcJGH hddg GdMeO hGdefI hGdUdGI Ydi GdfHi GdeUWai hBdg hGdSdGe s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdfMhs